2018
DOI: 10.1371/journal.pone.0197161
|View full text |Cite
|
Sign up to set email alerts
|

A clinical nursing rotation transforms medical students’ interprofessional attitudes

Abstract: This study explores the extent to which a one-week nursing rotation for medical students changed the interprofessional attitudes of the participating nurses and students. Third-year medical students worked with nurses before starting clinical rotations. Pre- and post-experience surveys assessing perceptions of mutual respect, nurse-doctor roles, and interprofessional communication and teamwork were given to 55 nurses and 57 students. The surveys consisted of qualitative questions and a Likert scale questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…We could infer a definition in the majority of the remaining papers ( n = 13) based on the way they assessed respect. For instance, in the reviewed qualitative work, judgments about one’s worth and value were often coded as evidence of respect (e.g., Aase et al, 2014; Baggs & Schmitt, 1997; Butterworth et al, 2018; Weller et al, 2011). Similarly, quantitative work used survey scales that included items capturing judgments about one’s value and worth and whether a person’s input should be considered (e.g., “the extent to which team members feel valued and appreciated for their role on the team”; Singer et al, 2016, p. 569).…”
Section: Resultsmentioning
confidence: 99%
“…We could infer a definition in the majority of the remaining papers ( n = 13) based on the way they assessed respect. For instance, in the reviewed qualitative work, judgments about one’s worth and value were often coded as evidence of respect (e.g., Aase et al, 2014; Baggs & Schmitt, 1997; Butterworth et al, 2018; Weller et al, 2011). Similarly, quantitative work used survey scales that included items capturing judgments about one’s value and worth and whether a person’s input should be considered (e.g., “the extent to which team members feel valued and appreciated for their role on the team”; Singer et al, 2016, p. 569).…”
Section: Resultsmentioning
confidence: 99%
“…The nursing students associated with Factor II emphasized responsible attitudes. Responsibility is part of the nursing profession [ 24 ] and central to nurses’ professional attitudes because studies have shown a positive association between professional responsibility and patient care quality [ 10 ]. In this group, 61.9% experienced increased menstrual distress during clinical practice, but they had the lowest menstrual leave rates.…”
Section: Discussionmentioning
confidence: 99%
“…An authentic context has a significant impact on the ways students perceive their learning experiences. Nevertheless, there are various challenges for sustainable implementation of IPE, including (a) non-coordinated and strictly separate curricula of different health care professions, (b) an insufficient number of specifically qualified teaching staff, and (c) limited financial resources of the institutions [8,13,19,20].…”
Section: Professional Image Of Nurse and Professional Interdependencementioning
confidence: 99%
“…In the IPE of medical students with nurses during their clinical practice, the goal is for the students to learn and perform the functions of a nurse; consequently, it is important to clarify their understanding of the nurse's role [7]. For medical students, performing Healthcare 2021, 9, 963 2 of 11 the functions of nurses during interprofessional practice is a transformative way to learn interprofessional competencies [8].…”
Section: Introductionmentioning
confidence: 99%